Fortification of Potato Chips with Natural Plant Extracts to Enhance their Sensory Properties and Storage Stability - Rababah, Taha M.; Feng, Hao; Yang, Wade; Yucel, Sevil (WILEY, 2012)
This study evaluated the effectiveness of grape seed extracts (GSE), green tea extracts (GTE), or butylated hydroxytoluene (BHT) on lipid oxidation reduction of potato chips stored for up to 90 days. The highest (P a parts per thousand currency sign 0.05) phenolic contents were detected in GSE (6134.5 mg gallic acid equivalent/100 g) followed by GTE and other plant extracts (oregano, thyme, terebinth, parsley, and bouncing bet). BHT had the greatest antioxidant activity (% inhibition) value (53.0) followed by GSE (42.6) and GTE (31.7). The GSE and GTE exhibited significantly higher antioxidant activities (measured by oxidative stability instrument) than the other plant extracts. The BHT and GSE at 1,000 ppm level was significantly the most effective in minimizing the peroxide value development during 90 days of storage. Descriptive results showed that higher levels of GSE and GTE (750 and 1,000 ppm) prevented the astringency development during 60 days of storage and minimized the off-notes, i.e., astringency and rancidity, during 90 days of storage. The cardboard attribute was not noticed when GSE and GTE, and BHT were added at 750 and 1,000 ppm levels. The GSE and GTE have a great potential for use as natural antioxidants to preserve the potato chips.
Keywords: Potato chips; Lipid oxidation; Sensory; Antioxidants; ANTIOXIDANT ACTIVITIES; TOTAL PHENOLICS; GRAPE SEED; PALM OLEIN; ROSEMARY; QUALITY; OIL; FENUGREEK; FOODS; Chemistry; Food Science & Technology